2023
DOI: 10.5194/bg-20-3803-2023
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution data reveal a surge of biomass loss from temperate and Atlantic pine forests, contextualizing the 2022 fire season distinctiveness in France

Lilian Vallet,
Martin Schwartz,
Philippe Ciais
et al.

Abstract: Abstract. The frequency and intensity of summer droughts and heat waves in Western Europe have been increasing, raising concerns about the emergence of fire hazard in less fire-prone areas. This exposure of old-growth forests hosting unadapted tree species may cause disproportionately large biomass losses compared to those observed in frequently burned Mediterranean ecosystems. Therefore, analyzing fire seasons from the perspective of exposed burned areas alone is insufficient; we must also consider impacts on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…The validation of the 2017 EFFIS BA map showed that the latter presented the highest omissions of all the assessed BA products, which resulted in a considerable underestimation of the total BA, plus a smoothing effect on fire perimeters that roughly delineated the burned patches. These inconsistencies have been previously reported in [40,91,92], and are attributed mainly to the 250-m coarse-resolution input data from MODIS used to generate the EFFIS product. On the other hand, GABAM is, to date, the only available global high-resolution BA product to provide BA mapping at finer spatial resolution to reliably detect smaller burned patches [32].…”
Section: Discussionmentioning
confidence: 57%
“…The validation of the 2017 EFFIS BA map showed that the latter presented the highest omissions of all the assessed BA products, which resulted in a considerable underestimation of the total BA, plus a smoothing effect on fire perimeters that roughly delineated the burned patches. These inconsistencies have been previously reported in [40,91,92], and are attributed mainly to the 250-m coarse-resolution input data from MODIS used to generate the EFFIS product. On the other hand, GABAM is, to date, the only available global high-resolution BA product to provide BA mapping at finer spatial resolution to reliably detect smaller burned patches [32].…”
Section: Discussionmentioning
confidence: 57%
“…An assessment of these fires in France, based on Sentinel-2 observations of burned area at a 10m resolution and a 10 m map of impacted biomass density derived from Global Ecosystem Dynamics Investigation (GEDI) height and French National forest inventory (NFI) plot data was produced by Vallet et al 60 . In their study they did not calculate emissions, but biomass lost from fires.…”
Section: Resultsmentioning
confidence: 99%
“…In their study they did not calculate emissions, but biomass lost from fires. Emissions of carbon gases and aerosols to the atmosphere should represent at most 50% of the biomass lost 60 , given typical combustion completeness factors. Our best estimate of biomass loss derived from this study is of 0.5 Tg C y −1 .…”
Section: Resultsmentioning
confidence: 99%
“…With the increased resolution of and precision in measuring tree height [43] and the tree crown area [44] at the regional scale with remote sensing, local allometric relationships will allow for landscape-scale applications of tree compartment assessments [45]. From this information, at a fine resolution and over extended areas, Fire 2024, 7, 204 12 of 17 regional impacts [15] and ecosystem vulnerabilities to fires could then be easily evaluated to drive post-fire management and restoration plans.…”
Section: Allometric Equations and Regional Applicationsmentioning
confidence: 99%
“…Availability of fruits (cones) can delay regeneration, and low crown base height can increase new crown fire likelihood. Although fine resolution remote sensing now allows for large scale biomass potential loss assessments [15], some key aspects of the amount of biomass within organs and resistance/regeneration potentials based on bark thickness or seed mass are hardly ever assessed or are only derived from generic allometric equations. Numerous studies have been conducted to estimate the pine aboveground biomass in Mediterranean countries, such as Pinus pinea in Italy [16], Pinus brutia in Turkey [17], or Pinus halepensis and Pinus nigra in Spain [18], among others.…”
Section: Introductionmentioning
confidence: 99%